Effect of Modified Breathing Exercise to Improve Abdominal Strength in Caesarean Section Women - Dasarapu, Indrani; Jagatheesan, Alagesan; Prathap, Suganthirababu; Dubba, NagaRaju; Vishu Priya, Suresh (INTI International University, 2023)
Background: The present National Policy for Health Promotion places a strong emphasis on raising public awareness of the importance of various forms of health and exercise. The women musculoskeletal system is impacted by several physiological events that take place during pregnancy. The inter-recti distance (IRD) typically increases and the abdominal muscles are stretched greatly which weakens the abdominal muscles. One of the lives saving procedures used on women most frequently today is a caesarean section (CS) for delivery. Objective: To evaluate the effect of modified Breathing Exercise and Abdominal Draw-in Maneuver to improve Abdominal strength in Post CS Women. Methods: A single blinded pilot randomized controlled trial was conducted on CS women. Post CS women were divided into 2 groups, that is group ADM (Abdominal Draw-in Maneuver) and group CBE (Corset Breathing Exercise) based on inclusion and exclusion criteria. The outcomes used in the study were pressure biofeedback unit and Abdominal curl test. Group ADM are treated with Abdominal Draw-in Maneuver and group CBE treated with Corset Breathing Exercise. Result: The result of the study showed that there was a significant difference between the groups. Statistical analysis of posttest vales of pressure biofeedback unit and Abdominal curl test revealed that post CS women who received Corset Breathing Exercise in group CBE showed marked improved compared to group ADM, the p value for both the outcomes are less than 0.001(P< 0.001). Conclusion: This study concluded that both groups ADM and CBE resulted in positive outcomes but group CBE with Corset Breathing Exercise showed more positive outcome in improving abdominal muscle strength.